The Effect of Online Visual Merchandising on Impulse Buying of Online Food Products Among Shopee Users: The Mediating Role of Site Trust - Kawet, Raymond Ch.; Raintung, Michael Ch.; Lumantow, Rudie Yobie (Sam Ratulangi University, 2026)
This study examines the effect of online visual merchandising on consumer impulse buying of online food products among Shopee users in Manado City, Indonesia, and tests the mediating role of site trust. A quantitative survey approach was employed using structured questionnaires measuring three constructs: visual merchandising, site trust, and impulse buying. Data were analyzed using regression-based mediation procedures in SPSS. The usable dataset consisted of 75 respondents. The findings indicate that online visual merchandising has a positive and significant effect on impulse buying, suggesting that attractive and informative digital product presentation (e.g., layout, images, and presentation cues) increases consumers’ tendency to make unplanned purchases. Visual merchandising also positively influences site trust. When site trust is included in the impulse buying model, it remains a significant predictor and reduces the direct effect of visual merchandising, indicating that site trust mediates the relationship between visual merchandising and impulse buying. These results highlight that effective visual merchandising not only stimulates impulsive purchase behavior directly but also indirectly by strengthening consumers’ trust in the platform. Practically, marketplace platforms and sellers should optimize visual presentation while simultaneously reinforcing trust-related signals (e.g., perceived security, reliability, and platform credibility) to encourage purchases without undermining consumer confidence. Keywords: impulse buying; Shopee; site trust; online food products; online visual merchandising